OPTIMALISASI MANAJEMEN LINGKUNGAN HIDUP UNTUK MENINGKATKAN KARAKTER SISWA MI NURUL MUN’IM - Fira Purwasih; Abdurrahman Abdurrahman (Jurnal Manajemen Pendidikan, 2026)
The ecological crisis and student’s low awareness of environmental cleanliness indicate the importance of strengthening environment-based character education in primary school, particularly in Islamic elementary school (madrasahs). However, most environmental management practices in school are still technical in nature and have not been systematically integrated with students’ character development. This study aims to examine the optimization of environmental management in fostering students’ character at the Islamic elementary school level. The study employed a qualitative approach with a case study design conducted at MI Nurul Mun’im. Data were collected through field observations and interviews with the principal, teachers, and students. The findings reveal that the optimalization of environmental management in character formation is implemented through four main mechanisms: environmental awareness socialization, teachers’ role modeling in wasted management practices, the implementation of reward and punishment as behavioral reinforcement, and the habituation of structured and sustainable cleanliness activities. This study contributes to the environment of a character-based environmental management model that integrates managerial, pedagogical, and religious aspects in fostering an environmentally responsible school culture at the Islamic elementary school level.